2020
DOI: 10.1007/s40200-020-00518-z
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of honey on low-density lipoprotein cholesterol and adiponectin concentrations in patients with type 2 diabetes: a randomized controlled cross-over trial

Abstract: Background: Due to antioxidant and fructose content, honey may be a suitable sweetener for patients with type 2 diabetes. The aim was to investigate the long-term effect of natural honey on oxidative and inflammatory status of patients with type 2 diabetes. Methods: In a randomized controlled cross-over trial, 43 patients with type 2 diabetes were allocated to either natural honey (50 g/day) plus dietary recommendations or only dietary recommendations for 8 weeks with one month washout period in between. Dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…e current results showed that both high-dose and low-dose HPA could significantly improve the abnormalities of serum lipids and liver lipids (TC, TG, and FFA) caused by alcohol (versus MG, Figures 1(a)-1(h)). HPA could obviously reduce the content of LDL-C and increased the content of HDL-C; this result was consistent with the study of Sadeghi et al [28]. Highdose HPA had the best effect in improving blood lipids.…”
Section: Discussionsupporting
confidence: 91%
“…e current results showed that both high-dose and low-dose HPA could significantly improve the abnormalities of serum lipids and liver lipids (TC, TG, and FFA) caused by alcohol (versus MG, Figures 1(a)-1(h)). HPA could obviously reduce the content of LDL-C and increased the content of HDL-C; this result was consistent with the study of Sadeghi et al [28]. Highdose HPA had the best effect in improving blood lipids.…”
Section: Discussionsupporting
confidence: 91%
“…[17] The last study was done by Sadeghi et al among 43 patients with T2DM using cross-over design . [28] Consumption of 50 g/day of honey for 8 weeks did not change any of the lipid profile parameters including TC, TG, LDL, and HDL (P > .05).…”
Section: Effects Of Natural Honey Consumptionmentioning
confidence: 84%
“…Eligible studies were conducted between 2007 and 2020, and the mean age of the participants was between 22 and 63. Of 23 included articles, 6 recruited healthy subjects , [13][14][15][16][17][18] while 11 were conducted among diabetic or pre-diabetic patients , [8,[19][20][21][22][23][24][25][26][27][28] and others included patients with chronic kidney disease (CKD) , [29] dry eye disease , [30] hypercholesterolemic patients , [31] nonalcoholic fatty liver disease (NAFLD) , [32] and overweight subjects . [33,34] Studies were mostly conducted in Iran (n = 14) [8,16,17,19,20,22-28,,3233] or Japan (n = 4) , [13,14,21,30] and the others were carried out in Brazil , [29] Chile , [15] Turkey , [18] Slovenia , [34] and Taiwan .…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest meta-analysis on ten trials revealed the beneficial effects of honey on lipid profiles, including LDL-cholesterol, TAG and HDL-cholesterol (14) . However, some recent studies have not confirmed the lipid-lowering properties of honey (15,16) . Despite the numerous potential biological activities mentioned above, the real effects of honey consumption on cardiovascular systems and lipid profiles are still a matter of debate.…”
mentioning
confidence: 97%